Surgical treatment of gastric cancer - Ruiz, Eloy (2021)
Forpatients with Localized Gastric Cancer(T1-4, N0-3, M0) the oncologic resection of the tumoris the only potentially curative treatment. The oncologic resection is necessary to achieve two objectives: a) Extirpation of the tumorwith free margins and b) Resection of regional lymph nodes. Due to the heterogeneity of gastric cancer, the type of gastric resection (mucosectomy, gastrectomy orextended gastrectomy) and lymphadenectomy (D2, D1, D2) depends of the depth of invasion of the gastric wall and the possibility of lymph node metastases. Therefore, using all methods of diagnosisthe ,clinical TNM (cTNM) has to be established in the pre-operative period in orderto perform a stage oriented resection.